The Influence of Staff Satisfaction and Workload on Service Quality at Aryaduta Suite Semanggi Hotel - Anda Suhanda; Hendaris Adriyanto; Rochiyat Setiawan (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This research is motivated by the importance of service quality within organizations, which is often hindered by employee dissatisfaction resulting from excessive workloads and unsupportive work environments. The objective of this study is to analyze the simultaneous influence of Job Satisfaction and Workload on Service Quality. The research employs a quantitative approach using multiple linear regression analysis. Data were collected from 36 respondents and processed using statistical software to test the model's significance and the strength of the relationships between variables. The results indicate that Job Satisfaction and Workload simultaneously have a significant effect on Service Quality, with an F-statistic of 26.644 and a significance level of 0.000. The coefficient of determination (R-squared) of 0.375 suggests that these two variables explain 37.5% of the variation in Service Quality, while the remaining 62.5% is influenced by factors outside the research model. The relationship between the variables is categorized as moderately strong, with an R-value of 0.612. Based on these findings, it is recommended that organizational management conduct routine evaluations of workload distribution to ensure a balanced distribution of tasks for all staff. Furthermore, the organization should address psychological and work environment factors to enhance employee satisfaction, which will ultimately have a positive impact on sustainable service quality improvement.